Chains of fortune: linking women producers and workers with global markets - Commonwealth Secretariat; Carr, Marilyn (2004)
Globalisation opens up new economic opportunities if poor women producers and workers are enabled to take advantage of them. The need for assistance differs between independent producers on the one hand and wage workers in export industries on the other. In the former case, the need mainly is for increased access to global markets. In the latter case, the need mainly is for better organising so as to bargain for better wages and working conditions. This edited volume brings together six case studies. Three link local producers with global markets: a cocoa cooperative in Ghana; an organic coconut oil producer in Samoa; and small enterprises in Mozambique. Three focus on improving the working conditions of wage workers in global value chains: those in the fruit exporting industry in South Africa; those in the garment export industry in Bangladesh; and those in the newly created call centres in India. Each case study is written by a team of international and national researchers and aims to present decision makers with concrete examples which can spread the gains of globalisation to the working poor through shifting the balance of access, power and returns within global value chains.
OCLC: 929085505
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA